Prevalence of human papilloma virus 16 and 18 in oral squamous cell carcinoma patients: A systematic review - Tariq, Ahmer Bilal; Huda, Noor Ul; Aman, Muhammad; Butt, Hira; Shumyle, Dur E; Khan, Nauman Rauf (Infectious Diseases Journal of Pakistan, 2023)
Background: HPV 16 and 18 are the two strains of Human Papillomavirus that have been associated with the development of OSCC. The aim of this study was to assess the prevalence of HPV 16 and18 in Oral Squamous Cell Carcinoma patients in comparison to controls. Data Sources: Literature search was conducted on PubMed, Scopus, and Google Scholar. All relevant studies till May 2025 were included. The search strategy combined Medical Subject Headings and relevant keywords. PRISMA guidelines were followed. Study Selection: Studies conducted on OSCC patients in which prevalence of HPV 16 and 18 was studied in comparison to controls were included. Studies that assessed the prevalence of HPV 16 and 18 in HNSCC, pre-malignant lesions, any other carcinoma and or strain of HPV other than 16 and 18 were excluded. Data Extraction: Data included publication title, year, authors, study design, sample size, prevalence of HPV 16 & 18 in cases and controls, number of cases and controls and detection methods. Quality assessment was done using Newcastle Ottawa scale. Data Synthesis: HPV 16 had higher prevalence in OSCC patients as compared to controls. Both the virus strains were seldom found in healthy controls. Conclusion: HPV 16 can have a significant role to play in OSCC development. HPV 16 (and HPV 18 to a lesser extent) is more prevalent in OSCC. Therefore, it may not be the primary cause but it has role to play in the development of OSCC. Keywords: Oral Squamous Cell Carcinoma, Human Papilloma virus, Polymerase chain reaction